707 Reducing school bullying with theatre and art. (1st September 2016) - Peek-Asa, Corinne; Ramirez, Marizen; Fawcett, Jennifer
Abstract : Background: Bullying is the most common form of school violence worldwide. School-based bullying prevention programs have shown varying success, and new, innovative programs with a stronger evidence base are needed. Arts-based programming, which appeals to the active emotional brains of adolescents, is a promising approach. Description of the program: Injury prevention researchers and a theatre group collaborated to develop a play called "Out of Bounds, " informed by qualitative and policy research. The play tells the story of a cyberbullying event and promotes themes of forgiveness, friendship, identity and labels. "Out of Bounds" was performed in ten Iowa middle and high schools and has more recently been on a national tour. Because viewing a play is unlikely to support behaviour change on its own, the team developed a program of arts-based activities to accompany the play. The activity toolkit is called "HEAR: Helping Educators use Art to Reduce Bullying." Activities were developed for multiple age groups and multiple settings, including classrooms and after school programs. Activities include games, acting, photovoice, reflective writing, drawing, and appreciative inquiry. Results: The play and toolbox were pilot tested through a service learning course with public health students and a school district. The play was performed in eight schools, and teachers chose activities from the toolkit to implement in their classrooms. Service learning students assisted with the activities. Through an online evaluation survey, over 90% of teachers assessed the program as very positive. One activity was assessed as neutral by all teachers, and this activity was revised. Teachers reported that 75% to 90% of students were highly engaged Conclusions: Schools rarely use arts-based approaches to target behaviour change, although they are a promising approach and schools increasingly seek ways to integrate arts into core education.